1996
DOI: 10.3382/ps.0751221
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Influence of Dietary Flaxseed Variety, Level, Form, and Storage Conditions on Egg Production and Composition Among Vitamin E-Supplemented Hens

Abstract: Trial 1 tested the effects of ground vs whole flaxseed at dietary levels of 5, 10, or 15% compared to a corn-soybean or fish oil control on egg production of Leghorn hens over a period of 8 wk. Dietary flaxseed decreased feed consumption, weight gain, and egg weights compared to the control diets; however, flaxseed and fish oil significantly improved egg production (88.9 and 93.0%, respectively) compared to the control (83.1%). Incorporation of linolenic acid (C18:3n-3) into the egg increased linearly as the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
120
3
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 10 publications
24
120
3
10
Order By: Relevance
“…He also suggested that n-3 PUFA could affect circulating estradiol. Similarly, Scheideler and Froning (1996) observed that the decrease in egg size was accompanied by a decrease in plasma estradiol concentration and postulated a nutritional control of the dietary long-chain fatty acids on the hormonal metabolism of the birds. These effects could partially explain the lower egg weight found in birds fed 3.5% and 5.0% fish oil in the current experiment.…”
Section: --mentioning
confidence: 92%
“…He also suggested that n-3 PUFA could affect circulating estradiol. Similarly, Scheideler and Froning (1996) observed that the decrease in egg size was accompanied by a decrease in plasma estradiol concentration and postulated a nutritional control of the dietary long-chain fatty acids on the hormonal metabolism of the birds. These effects could partially explain the lower egg weight found in birds fed 3.5% and 5.0% fish oil in the current experiment.…”
Section: --mentioning
confidence: 92%
“…(1994) found significant differences in yolk and egg weight when feeding menhaden oil at 30 g kg -1 . Scheideler and Froning (1996) found increased henday egg production but a decrease in yolk size of eggs from hens fed 15 g kg -1 of fish oil. Both Whitehead et al (1993) and Scheideler and Froning (1996) described the decrease in yolk size as an effect of the long-chain fatty acids on the estrogen activity of the hen.…”
Section: Egg Productionmentioning
confidence: 99%
“…Scheideler and Froning (1996) found increased henday egg production but a decrease in yolk size of eggs from hens fed 15 g kg -1 of fish oil. Both Whitehead et al (1993) and Scheideler and Froning (1996) described the decrease in yolk size as an effect of the long-chain fatty acids on the estrogen activity of the hen. The depression in egg weight by feeding high levels of fish fat, shown in the present study, confirms the finding of Herstad et al (2000) that egg weight was significantly reduced on diets containing 30 g kg -1 of fish oil.…”
Section: Egg Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it was noted that less food was consumed by hamsters fed fish oil-containing diets supplemented with vitamin E than unsupplemented diets, while BWG was not affected by vitamin E supplementation (Poirier et al, 2002). In a study conducted with layer hens, it was found that vitamin E supplementation at different levels to diets enriched with PUFAs did not affect performance (Meluzzi et al, 2000;Sijben et al, 2002) and in contrast to these studies, Scheideler & Froning (1996) noted that vitamin E supplementation (50 IU/kg) to a diet enriched with n-3 PUFAs significantly improved egg production in layer hens. While some reports (Coetzee Guo et al, 2001;Özkan et al, 2007) describe a lack of response in performance to supplementation with vitamin E under normal conditions, others have shown improvements in performance.…”
Section: Resultsmentioning
confidence: 64%